5 - La différence dans le système du même. Contribution philosophique à l’approche genre - Béatrice Faye (Africa Development, 2007)
Reflections on male–female relations have gone through important stages, each of which corresponds to a specific predominant theoretical model. Starting from a ‘one-dimensional’ model rooted in the biological dimension, researchers devel- oped ‘multi-dimensional’ models to describe the increasing complexity of gender categories and its components. In the history of economics, gender-based divi- sion of labour is seen as natural, just as the biological discrimination between genders. More specifically, it is worth noting that economic theories generally remain silent about how social relations affect economic development. So, it is not surprising that conventional economics is neither well suited to address the most crucial issues of development, nor more relevant either to explain the male–female social relations. It is more of a hindrance than an instrument to analyse such relations. Indeed, by ending discrimination in roles while systematically partici- pating in all the formerly male-reserved activities, women have swept away the universally-assumed characteristic of males: the superiority of men over women. Women could express a sense of belonging to a group defined, for example, not in terms of class distinction, but based on gender categories, although such ‘gender consciousness’ is often articulated around the idea of women’s superiority as household managers, agents of social cohesion, and guardians against state excesses.